Rural-Urban Differences in Health Care Expenditures: Empirical Data from US Households - Wei-Chen Lee; Luohua Jiang; Charles D. Phillips; Robert L. Ohsfeldt (Hindawi Limited, 2014)
Purpose. To estimate the rural-urban differences in expenditures of outpatient care, hospital inpatient care, hospital emergency room services, medications, and total services. Methods. This cross-sectional study used data from the 2010 Medical Expenditure Panel Survey. The overall sample size for the study was 22,772. Weighted frequencies, means, or percentages were estimated to illustrate the distribution of each variable. Five two-part utilization models were then fit to determine the likelihood of having nonzero expenses and to identify how residence in a rural versus urban area affected expenditures in our five expense categories. Quantile regressions were estimated to further explore relationships between residence and each quantile of nonzero expenditure. Results. The results of two-part model suggest that rural populations spent more on medications, while urban populations spent more on emergency care. However, no rural-urban difference was found in total health expenditures. The results of quantile regressions suggest that the highest users (at the upper quantiles) of medication and total expenditure experienced the strongest positive effects of living in rural areas. Conclusions. Total health expenditures do not seem to vary significantly across urban and rural areas. However, rurality does have important effects on those who make the most use of outpatient care and prescription medications. Reviewing total health expenditures for urban and rural populations is not enough. Policymakers should monitor the effects of geographic differences, especially in the highest expenditure quantiles, for specific types of health expenditures. Differences in the influence of rurality across this distribution of health expenditures may provide important guidance for interventions.